2016
DOI: 10.1155/2016/5078627
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Regulation of Endothelial Junction Proteins and Clinical Consequence

Abstract: Cellular junctions play a critical role in structural connection and signal communication between cells in various tissues. Although there are structural and functional varieties, cellular junctions include tight junctions, adherens junctions, focal adhesion junctions, and tissue specific junctions such as PECAM-1 junctions in endothelial cells (EC), desmosomes in epithelial cells, and hemidesmosomes in EC. Cellular junction dysfunction and deterioration are indicative of clinical diseases. MicroRNAs (miRNA) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 46 publications
0
48
0
Order By: Relevance
“…We found increased levels of miR‐98 in EVs isolated from the culture medium of embryo IVP in high compared to low oxygen tension. The miRNA‐98 regulates negatively tight junction mRNAs reducing protein levels (Zhuang, Peng, Mastej, & Chen, ). These results suggest that high oxygen tension has a detrimental effect on delivered microRNAs mediated by EVs and might be involved in delayed embryo development during the implantation phase.…”
Section: Discussionmentioning
confidence: 99%
“…We found increased levels of miR‐98 in EVs isolated from the culture medium of embryo IVP in high compared to low oxygen tension. The miRNA‐98 regulates negatively tight junction mRNAs reducing protein levels (Zhuang, Peng, Mastej, & Chen, ). These results suggest that high oxygen tension has a detrimental effect on delivered microRNAs mediated by EVs and might be involved in delayed embryo development during the implantation phase.…”
Section: Discussionmentioning
confidence: 99%
“…The miRNAs corresponding to 7 CG sites associated with HCC vascular infiltration (hsa‐miR‐200c, hsa‐miR‐345, hsa‐miR‐9‐1, hsa‐miR‐15b, hsa‐miR‐107, hsa‐miR‐199a‐3p, and hsa‐miR‐184) were screened with the LASSO‐Logistic method and are closely related to angiogenesis 38–42 . Ghosh et al 39 found that miR‐199a‐3p was directly involved in HCC angiogenesis, invasion, and metastasis, and it inhibits the angiogenesis of HCC by inhibiting the expression of VEGF and its receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Claudin‐5, as a member of Claudins family, is specifically expressed in endothelial cells different from epithelial cells . These two cell junction‐related proteins constitute the tight junction of endothelial cell‐cell tight junction (TJ) and maintain the stabilization of endothelial permeability and vascular endothelial barrier . SACC‐83 cell‐derived exosomes downregulated ZO‐1 and Claudin‐5 in endothelial cells destroyed the integrity of endothelial barrier.…”
Section: Discussionmentioning
confidence: 99%